Flow cytometric measurement of STAT5 phosphorylation in cytomegalovirus‐stimulated T cells. Issue 8 (20th December 2020) - Bitar, Michael; Boettcher, Marcus; Boldt, Andreas; Hauck, Fabian; Köhl, Ulrike; Liebert, Uwe G.; Magg, Thomas; Schulz, Marian S.; Sack, Ulrich
Abstract: Cytomegalovirus (CMV)‐specific T cells expand with CMV reactivation and are probably prerequisite for control and protection. Given the critical role STAT5A phosphorylation (pSTAT5A) in T cell proliferation, this study presents a simple and sensitive flow cytometric‐based pSTAT5A assay to quickly identify CMV‐specific T cell proliferation. We determined pSTAT5A in T cells treated with CMV‐specific peptide mix (pp65 + IE1 peptides) from 20 healthy adult subjects and three immunodeficient patients with CARMIL ‐2 mutation. After stimulation, the percentage of pSTAT5A + T cells in CMV‐seropositive (CMV + ) subjects significantly increased from 3.0% ± 1.9% (unstimulated) to 11.4% ± 5.9% (stimulated) for 24 h. After 7 days of stimulation, the percentage of expanded T cells amounted to 26% ± 17.2%. Conversely, the percentage of pSTAT5A + T cells and T cell proliferation from CMV‐seronegative (CMV − ) subjects hardly changed (from 3.0% ± 1.3% to 3.7% ± 1.8% and from 4.3% ± 2.1% to 5.7% ± 1.7%, respectively). We analyzed the correlation between the percentage of pSTAT5A + T cells versus (1) CMV‐IgG concentrations versus (2) the percentage of expanded T cells and versus (3) the percentage of initial CMV‐specific T cells. In immunodeficient patients with CARMIL‐2 mutation, CMV‐specific pSTAT5A and T cell proliferation were completely deficient. In conclusion, flow cytometric‐based pSTAT5A assay represents an appropriate tool to quickly identify CMV‐specific T cell proliferation and helps to understand dysfunctions in controlling other pathogens. Flow cytometric‐based pSTAT5A assay may be a useful test in clinical practice and merits further validation in large studies.